STANDARDIZATION AND SENSORY EVALUATION OF ANTIOXIDANT ENRICHED PASTA WITH TANNER’S CASSIA (SENNA AURICULATA) AND SPINACH (SPINACIA OLERACEA L.) - K. Suvalakshmi; P. Sivakumar; K.S. Gnanalakshmi; M. Easther Magdalene Sharon (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Spinach and Tanner’s cassia, both are nutrient-dense leafy plants known for their high fibre and antioxidant content, making them valuable additions to a healthy diet and for overall wellbeing. This study was aimed to develop antioxidant rich  pasta  by  incorporating  spinach  powder  (Spinacia  oleracea  L.)  and  Tanner’s Cassia (Senna auriculata) flower extract. Five distinct formulations were formulated, including a control (100% Maida) and four treatments (T1–T4) with varying levels of spinach powder (5%, 10%, 15% and 20%) and Tanner’s Cassia flower extract (50 mL, 55 mL, 60 mL, 65 mL). Sensory evaluation was conducted using a 9-point hedonic scale to assess the appearance, texture, flavor, taste and overall acceptability. The results of this study showed that T2 (10% spinach powder) was the most preferred formulation, receiving the highest sensory scores across all attributes. The control and T2 (10% spinach powder) pasta samples showed notable differences in proximate composition and antioxidant activity. Antioxidant activity, assessed through the DPPH radical scavenging method and all treatment samples (T1, T2, T3 and T4) exhibited a significant increase (71%, 74%, 77.7% and 80%) compared to the control sample (2.0%). T2 and the control sample had higher levels of protein (12.23 ± 0.005% and 9.72 ± 0.002%), fat (3.98 ± 0.005% and 0.977 ± 0.004%), dietary fibre (6.86 ± 0.004% and  1.27 ± 0.004%)  and  ash  content  (4.42 ± 0.007%  and  0.82 ± 0.004%),  while carbohydrate    content  was  lower  (65.85 ± 0.02%  and  80.07 ± 0.002%)  during  the comparative assessment. This study suggests that pasta enriched with 10% spinach powder  and  Tanner’s  Cassia  flower  extract  (55  mL)  can  serve  as  a  functional food, offering enhanced nutritional and health benefits with higher consumer acceptability, as supported by both sensory evaluation and antioxidant activity results.